Prostate Specific Antigen Level and Gleason Score in Indonesian Prostate Cancer Patients - Herawan, Muhammad Imam Al Kautsar; Adriansjah, Ricky (Majalah Kedokteran Bandung, 2024)
In Indonesia, the number of prostate cancer continues to increase and even becomes the most common malignancy in men in 2015. Delayed early detection of prostate cancer is a significant concern. Prostate-specific antigen (PSA) level is found to be elevated in various conditions of prostate tissue damage, including prostate cancer. The extent of tissue damage in prostate cancer, represented by the Gleason score, is suspected to be related to the increase in the PSA level in the bloodstream. To investigate the relationship between the PSA level and Gleason scores in prostate cancer patients, a cross-sectional observational study was conducted. The study population consisted of 83 prostate cancer patients treated in Dr. Hasan Sadikin General Hospital Bandung, Indonesia, from 2017 to 2021. Data collected were analyzed using Spearman correlation test was used with an alpha value of 5%. Results indicated that 37.3% patients had a PSA level above 200 ng/dL, and 25.3% had a PSA level between 10-50 ng/dL. The majority of patients (48.1%) had a Gleason score of 9-10 (ISUP 5), while 24.1% had a score of 8 (ISUP 4). Bivariate analysis showed no significant relationship between the PSA level and Gleason score (p-value=0.445). Further studies are needed to determine the sensitivity and specificity of PSA in diagnosing prostate cancer.